Rūmī and the hermeneutics of eroticism - Tourage, Mahdi. (Iran Studies, 2007)
This is the first systematic examination of the esoteric significance of the bawdy tales and explicit sexual passages present in Rūmī's (d. 1273) Mathnawī , a masterpiece of medieval Perso-Islamic mystical literature and theosophic teachings. Using the relevant features of postmodern theories as strategic conceptual tools, and drawing on the recent interpretations of medieval kabbalistic texts, it is a fascinating examination of the link between the dynamics of eroticism and esotericism operative in Rūmī's Mathnawī . In some of these bawdy tales, the phallus is used as an esoteric symbol. The book concludes that these tales are used primarily to communicate esoteric secrets, particularly when this communication is contemplated along gender lines, mediated through erotic imagery, or expressed in sexual terms.